2020
DOI: 10.1038/s41598-020-66406-x
|View full text |Cite|
|
Sign up to set email alerts
|

Discordance for genotypic sex in phenotypic female Atlantic salmon (Salmo salar) is related to a reduced sdY copy number

Abstract: the master sex determinant in rainbow trout (oncorhynchus mykiss), sexually dimorphic on the Y chromosome (sdY), is strongly but not perfectly associated with male phenotype in several other species from the family Salmonidae. currently, the cause and implications of discordance for sdYpredicted genotypic sex and phenotypic sex in these species is unclear. Using an established multiplex PCR test for exons 2 and 3 of sdY, we demonstrated that sdY-predicted genotypic sex was discordant with histologically eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 48 publications
(60 reference statements)
1
15
0
Order By: Relevance
“…These fish originated from three dams and five sires among the 88 parents. The number of discordant females observed here is higher than the 1% frequency observed in a domesticated Tasmanian Atlantic salmon strain ( Eisbrenner et al, 2014 ; Kijas et al, 2018 ) but similar to the 7% recently reported for the same Tasmanian strain ( Brown et al, 2020 ). Given the inheritance model presented here, it is likely that this difference is merely the result of the number of affected parents and the cross design, although strain specific differences in the frequency of the pseudocopy of sdY cannot be ruled out.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…These fish originated from three dams and five sires among the 88 parents. The number of discordant females observed here is higher than the 1% frequency observed in a domesticated Tasmanian Atlantic salmon strain ( Eisbrenner et al, 2014 ; Kijas et al, 2018 ) but similar to the 7% recently reported for the same Tasmanian strain ( Brown et al, 2020 ). Given the inheritance model presented here, it is likely that this difference is merely the result of the number of affected parents and the cross design, although strain specific differences in the frequency of the pseudocopy of sdY cannot be ruled out.…”
Section: Discussionsupporting
confidence: 86%
“…Since the sdY gene was discovered ( Yano et al, 2013 ), different mechanisms have been invoked to explain the existence of discordant phenotypes such as phenotyping or sampling errors, environment mediated sex reversal, female-specific gene inactivation, sequence variability, the existence of minor sex determining (SD) genes and recombination ( Yano et al, 2013 ; Cavileer et al, 2015 ; Larson et al, 2016 ; EysturskarĂ° et al, 2017 ; King and Stevens, 2020 ). Recently, a dosage-dependent mechanism has been suggested to explain these discrepancies in Atlantic salmon ( Brown et al, 2020 ), suggesting that sdY is present in a single copy in the male genome and might be also present as partial copies in the female genome. However, our results strongly point to the existence of non-functional autosomal copies as previously suggested for two coregoninae species ( Yano et al, 2013 ) and sockeye salmon ( Larson et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also congruous with a previous study finding a high percentage of sdY-negative sockeye salmon males (~30%) in an upper Columbia River hatchery [ 27 ], and another study with similar findings in samples collected from Asian populations [ 147 ]. Atlantic salmon females have been identified with sdY, but likely have autosomal pseudocopies rather than a bonafide function sex-determining copy (bioRχiv [ 148 ]) [ 33 ]. This has been noted in other salmonid species as well [ 147 ].…”
Section: Discussionmentioning
confidence: 99%
“…Not all populations of sockeye salmon appear to have a strong association of sdY to sex [ 27 ] suggesting that an alternative sex-determination mechanism(s) may exist in certain populations. SdY-positive females in Atlantic salmon have been identified previously and explained as possible mosaicism, but sdY-negative males are less common and require another explanation [ 33 ].…”
Section: Introductionmentioning
confidence: 99%